Comparison of clinical characteristics and disease burden of febrile seizures in children with and without COVID-19 - Zhongli Jiang; Cuiyun Fang; Fengyimei Peng; Wei Fan (BMC, 2024)
Abstract Background Febrile seizures (FS) are the most common seizure disorder in children and a common neurologic complication in children with coronavirus disease 2019 (COVID-19). This study aimed to identify differences in clinical characteristics and disease burden between FS with and without COVID-19. Materials and methods We conducted a retrospective analysis of medical data at our hospital from December 2019 to July 2023, focusing on hospitalized patients under the age of 14 diagnosed with FS who underwent COVID-19 polymerase chain reaction (PCR) testing. Descriptive statistics and analysis of variance were employed to compare the COVID-19 and non-COVID-19 groups in terms of clinical characteristics and disease burden. Results A total of 514 patients were included, with 106 testing positive for COVID-19 and 408 testing negative. Patients with COVID-19 were older (34.87 ± 6.16 vs. 28.61 ± 11.35 months, P < 0.001) and had a higher proportion of males (79.2% vs. 62.3%, P = 0.001). The COVID-19 group had longer seizure durations (4.57 ± 4.38 vs. 3.22 ± 2.91 min, P = 0.006) and more complex FS (25.5% vs. 15.9%, P = 0.022). Laboratory tests showed lower lymphocyte counts in the COVID-19 group (1.87 ± 1.48 vs. 2.75 ± 1.51 × 103/µL, P < 0.001) and higher creatine kinase levels (158.49 ± 82.89 vs. 110.89 ± 56.11 U/L, P < 0.001). No significant differences were found in hospital costs, length of hospitalization, and intensive care unit admissions. Conclusion Clinicians should be knowledgeable about the distinct clinical characteristics of FS in children with COVID-19. Despite distinct features, the prognosis remains favorable and does not require excessive intervention. Ongoing monitoring and research are needed to fully understand the impact of COVID-19 on FS and optimize management strategies.